The traveling aquatic athlete - Derman, W. (FINA World Sports Medicine Congress, 18, 2016)
Prof. Wayne Derman, University of Cape Town (ZAF), talks about "The Traveling Aquatic Athlete: How to Keep Them Healthy" at the FINA World Sports Medicine Congress 2016 (30:59 min).